Komparasi Teknik Pengumpulan Data dan Pengembangan Instrumen Penelitian pada Pendekatan Kualitatif dan Kuantitatif:Kajian Sistematis - Adang Ridwan; Saputra, Yoga Erdi; Karmila, Ria; Septiawan, Rian (Concept: Journal of Social Humanities and Education, 2026)
The selection of appropriate data collection techniques and the development of valid research instruments are fundamental aspects that determine the quality and credibility of educational research. Differences in research paradigms between qualitative and quantitative approaches require distinct strategies for collecting data and designing research instruments. This study aims to compare data collection techniques and research instrument development in qualitative and quantitative research approaches through a systematic review. The study employed a systematic literature review method by analyzing relevant scientific publications, including journal articles, books, and conference proceedings published in the field of educational research. The collected literature was selected, evaluated, and synthesized based on predetermined inclusion and exclusion criteria to identify similarities, differences, strengths, and limitations of each approach. The findings indicate that qualitative research primarily employs interviews, observations, focus group discussions, and document analysis to obtain in-depth contextual data, while its research instruments include interview guides, observation protocols, field notes, and documentation guidelines that are developed flexibly according to research contexts. In contrast, quantitative research predominantly utilizes questionnaires, structured observations, tests, and experiments with standardized instruments that emphasize validity, reliability, and objectivity. The comparison further reveals that qualitative instrument development prioritizes credibility, transferability, dependability, and confirmability, whereas quantitative instrument development focuses on content validity, construct validity, criterion validity, and reliability testing. This study provides a comprehensive understanding of the characteristics of data collection techniques and research instrument development in both approaches, offering practical guidance for researchers in selecting appropriate methods based on research objectives and designs.